Coercion, conflict, and commodities - Cilliers, J (University of Oxford, 2013)
In this paper, I develop a general equilibrium model of violence to explain observed variation in coercive practices in conict zones. Armed groups own land in the resource sector and allocate military resources between conflict and coercion, which assigns defacto ownership over land and labour respectively. If find that coercion is higher if labour is scare relative to land, if production is labour-intensive, or if one group is dominant relative to others. Furthermore, the impact of the price of the commodity depends on the distribution of military strength: coercion increases with price if one group is dominant, but this effect is potentially reversed if military power is highly decentralised. These results are consistent with historic cases of the rise in serfdom in 16th century Russia, different coercive regimes in the rubber plantations in Amazonia and the Congo Free State 19th century, and also variation in coercion during the Sierra Leonean Civil War and in the eastern provinces of the Democratic Republic of Congo. Results of the model have implications for both trade and military policy. Trade policy aimed at reducing domestic commodity prices could actually lead to an increase in coercion. Similarly, a cease-fire agreement between armed groups can be interpreted as a form of collusion, as military resources are redirected from conflict to coercion.